2003
DOI: 10.1017/s0305000903005609
|View full text |Cite
|
Sign up to set email alerts
|

Subject realization and crosslinguistic interference in the bilingual acquisition of Spanish and English: what is the role of the input?

Abstract: This study investigated whether crosslinguistic interference occurs in the domain of subject realization in Spanish in a bilingual acquisition context. We were also interested in exploring whether the source of the interference is due to child-internal crosslanguage contact between English and Spanish, as is commonly assumed, or due to the nature of the language input in a bilingual family, a factor which has not typically been considered in studies of crosslinguistic influence. The use of subjects in a null s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
296
8
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 312 publications
(325 citation statements)
references
References 26 publications
19
296
8
2
Order By: Relevance
“…In addition to facilitation effects in bilingual acquisition, researchers have examined cross-linguistic influence between the languages of simultaneous bilingual children at the discourse-pragmatics syntax interface with respect to argument omission and pronominalization (Hulk (2000), Müller and Hulk (2001), Paradis and Navarro (2003), Serratrice, Sorace, and Paoli (2004)). Such cross-linguistic effects may be at the root of the skew in error types shown in Table 3 in which the bilingual children used more strong pronouns in direct object position than the monolinguals.…”
Section: Bilingual Versus Monolingual Childrenmentioning
confidence: 99%
“…In addition to facilitation effects in bilingual acquisition, researchers have examined cross-linguistic influence between the languages of simultaneous bilingual children at the discourse-pragmatics syntax interface with respect to argument omission and pronominalization (Hulk (2000), Müller and Hulk (2001), Paradis and Navarro (2003), Serratrice, Sorace, and Paoli (2004)). Such cross-linguistic effects may be at the root of the skew in error types shown in Table 3 in which the bilingual children used more strong pronouns in direct object position than the monolinguals.…”
Section: Bilingual Versus Monolingual Childrenmentioning
confidence: 99%
“…Much previous research on second language (L2) acquisition has focused on the influence of the L1 on the L2 (Argyri & Sorace 2007;Belletti et al 2007;Hertel 2003;Hopp 2009;Lozano 2006Lozano , 2009Montrul 2004a;Paradis & Navarro 2003;Rothman 2009;Serratrice et al 2011;Serratrice et al 2004;), but to a much lesser extent on the influence that the L2 might have in the native language (L1) of nonnative speakers. This phenomenon is known as 'L1 attrition', and it refers to the changes in a speaker's L1 as the result of the acquisition of an L2.…”
Section: Introductionmentioning
confidence: 99%
“…bilingual children, near-native speakers and L1 attriters). Previous research addressed aspects such as the effects of The final publication is available at Springer via http://dx.doi.org/10.1007/s10936-015-9372-4 4 semantic or discourse factors in the acquisition of word order (Belletti et al 2007;Hertel 2003;Hopp 2009;Lozano 2006;Montrul 2004a;Wilson 2009), or the influence of pragmatics in the acquisition of null versus overt pronominal subjects and objects (Argyri and Sorace 2007;Belletti et al 2007;Lozano 2009;Montrul 2004b;Paradis and Navarro 2003;Rothman 2009;Serratrice et al 2011;Serratrice et al 2004;Tsimpli et al 2004). Structures that are sensitive to pragmatic or contextual conditions have been an especially privileged ground for research.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehension data discussed in Orfitelli & Hyams (2012) shows that children assign a different interpretation to null subjects than adults during the null subject stage. It has been found that bilingual English-Spanish children overuse overt subjects in Spanish (Paradis & Navarro 2003). Overall, these results seriously question the view that macroparameters, even those as fundamental as V2 and the NSP, are acquired fast and without problems.…”
Section: The Status Of Macroparameters In Minimalismmentioning
confidence: 93%